Comparison of Clinical Data, CT, and Bone Histopathology in Unilateral Chronic Maxillary Sinusitis. Issue 1 (30th October 2012) - Joshua, Ben‐Zion; Sachs, Ofer; Shelef, Ilan; Vardy‐Sion, Netta; Novack, Lena; Vaiman, Michael; Puterman, Max
Abstract : Objectives: To evaluate bone changes demonstrated by computed tomography (CT) as a predictor of the severity of chronic rhinosinusitis. Study Design: Cross‐sectional study. Settings: Tertiary referral university medical center. Subjects and Methods: Thirty‐eight patients diagnosed with unilateral chronic maxillary sinusitis underwent endoscopic sinus surgery from 2003 to 2009. Preoperative CTs of all patients were reviewed by a single radiologist blinded to the pathologic diagnosis. Bone density was evaluated and expressed in Hounsfield units (HU). Sinus wall thickness (WT) was also measured and compared with the contralateral side. All the histopathologic specimens were reviewed. A database was constructed containing demographic data, clinical symptoms, CT measurements, and histopathologic findings. Results: Average age was 44.07 years, with 22 women (57.9%) and 16 men (42.1%). The average wall density (WD) was 828.7 HU, and no correlation was found between the density of the diseased maxillary sinus bony walls and the severity of the histopathologic inflammatory process of the soft tissue ( P =. 474). The average wall thickness of the diseased sinuses was 2.6 mm, and a correlation was found between inflammation severity and wall thickness ( P =. 018). Wall thickening was found in 97.3% of the cases and an increase in density in 78.9% without correlation between WD and WT. Conclusion: Wall thickness but not WD obtained from CT scans may be a simple index for evaluation of unilateral chronic rhinosinusitis and its severity. Further studies confirming these results and comparing them with clinical correlates are indicated.